Solar desalination system with a focal point concentrator using different nanofluids - Rafiei, A. (Elsevier Ltd, 2020)
In the current study, a solar desalination system was energetically and exegetically investigated using a focal point concentrator as the heat source of the desalination system. The desalination system consisted of photovoltaic thermal (PV) panels and Humidification Dehumidification Desalination (HDD) systems. The effect of nanofluid application as the solar working fluid on the desalination performance was investigated as the main objective of this study. Optical and thermal analyses of the solar desalination system were conducted by SolTrace and Maple software, respectively, whereas exergy analysis of the solar desalination system was performed by writing codes in the Maple software. Different oil-based nanofluids were used as the solar working fluids including Al2O3/oil, Cu/oil, CuO/oil, TiO2/oil and MWCNT/oil. Also, the influence of different PV-HDD parameters including water flow rate and water to air flow ratio was considered on the performance of the solar desalination system. The results revealed that the cavity heat gain and thermal efficiency increased with increasing nanofluid concentration for all of the investigated nanofluids. Also, the Cu/oil nanofluid showed the highest thermal performance among all of the nanofluids. Exergy gain and exergy efficiency of the investigated solar system decreased with increasing nanofluid concentration. Moreover, the Cu/oil nanofluid resulted in the lowest exergy efficiency compared to other investigated nanofluids. The application of the Cu/oil nanofluid with higher nanofluid concentration can be suggested for producing the highest amount of the freshwater production, and the lowest gain output ratio of the desalination system. Â© 2020 Elsevier Ltd